The leadership role of principals in managing HIV in primary schools in the Grahamstown District Area, Eastern Cape Province - Isaacs, Arthur James David (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.